TIME OF GOODS DELIVERY, FULLFILMENT OF AN OBLIGATION BY SELLER - Majlinda Belegu (European Scientific Journal, ESJ, 2014)
Contract parties have agreed the time of goods delivery based on the agreement that was reached between them.According to the legislation the time of goods delivery is determined in two ways: determination of the day (time), determination of date when the obligation is fullfiled. According to the first the day is determined by the agreemend of the parties and this day is connected to a determined day or to a determined event. Goods delivery is also done based on a precisely determined term based on the contract agreement and it has to be strict and respected by both parties. Apart to this, there are cases when contract parties do not determine the time for goods delivery, and they determine the time after the contract was signed and regarding this there are three ways of delivery.Delivery is done 8 days after the contract is signed, but the Law on Obligations and other legislations detrmine an addititional agreement to be signed between partis after the contract was signed.Delivery of goods on the determined day and time, means also the fulfilment of the contract therefore the fulfilment brings to a better development of trade and it does’t created delays from both parties. When there are no delays on goods delivery on the determined time then there are also no casualties.All this has an impact on improving the circulation of goods and in way perfection by which it is contributed to the business perspectives and to the circulation of goods.